Digital Da’wah as Dialogic Communication: A Media Psychology Approach to Audience Engagement on TikTok - Elvi Sumanti; Abdullah Abdullah; Efi Brata Madya (Universitas PGRI Yogyakarta, 2026)
The rapid growth of short-video platforms has transformed contemporary da’wah, especially on TikTok. This study examines digital da’wah as dialogic communication from a media psychology perspective, focusing on audience engagement. Using a qualitative design, it applies Fairclough’s Critical Discourse Analysis to selected Muslimah influencer content and audience interactions, supported by digital observation, content documentation, comment analysis, and in-depth interviews (NVivo-assisted). This research fills a gap by integrating media psychology, CDA, and Islamic communication to explain how discursive strategies generate psychological engagement in digital da’wah. Findings identify three dialogic patterns affirmative dialogue (supportive alignment), reflective dialogue (self-evaluative negotiation of values), and contested dialogue (critical questioning and boundary-setting). Emotional engagement is dominated by empathy, moral reassurance, and motivational uplift, which drives cognitive involvement through self-reflection and gradual internalization of Islamic values. Cyclical creator–audience interactions also shape ongoing religious meaning-making and Muslimah identity construction. Practically, effective TikTok da’wah should prioritize empathetic framing, prompts for reflection, and responsive comment management to strengthen sustained engagement. Keywords: audience engagement, dialogic communication, digital da’wah, media psychology, muslimah influencers, TikTok